The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/309093
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Silica-Supported Palladium Catalysts for Biofuel Upgrade

Abstract: We report the preparation of two hydrocracking catalysts Pd/CoMoO 4 /silica and Pd/CNTs/CoMoO 4 /silica (CNTs, carbon nanotubes). The structure, morphologies, composition, and thermal stability of catalysts were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy, transmission electron microscopy (TEM), energy-dispersive X-ray (EDX), and thermogravimetric analysis (TGA). The catalyst activity was measured in a Parr reactor with camelina fatty acid methyl esters (FAMEs) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The results of the present study revealed that the acid value of Ceiba pentandra oil was 89.49 mg KOH/g. The density (at 20 o C), kinematic viscosity (at 40 o C), and flash point of Ceiba pentandra oil were 0.891 g/cm 3 , 37.47 Cst and 308 o C, respectively.…”
Section: Physicochemical Analysis Was Performed Onmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of the present study revealed that the acid value of Ceiba pentandra oil was 89.49 mg KOH/g. The density (at 20 o C), kinematic viscosity (at 40 o C), and flash point of Ceiba pentandra oil were 0.891 g/cm 3 , 37.47 Cst and 308 o C, respectively.…”
Section: Physicochemical Analysis Was Performed Onmentioning
confidence: 96%
“…Continuous use of fossil fuels creates a negative impact on the environment such as accelerate global warming, CO2 emissions, greenhouse effects and air pollution and other environmental problems [1][2][3][4]. One of the efforts made to overcome the energy crisis is to develop fuel from sources of renewable energy, to develop fuel from new energy sources.…”
Section: Introductionmentioning
confidence: 99%